Web-Based GIS Software and Database Tools for Water Resources Management - Marwah Abduhadi Hasan; Falah Hassan Abed (Genius Journals, 2023)
Water is a precious natural resource that is in short supply. Thus, to ensure sustainable development, water resource management has become a critical component of global concern, particularly in arid and semi-arid countries. The field of open source GIS software has grown at a breakneck pace over the last few decades. This software quickly established a key and significant role in academic and applied research. The purpose of this study is to examine the characteristics and design of a Web GIS Platform for monitoring water resources in the study area to disseminate, exchange, and manage information via the internet. The platform-developed application demonstrates that by leveraging Open Source software and database tools, it is possible to create a flexible and interoperable tool for water resource management that provides critical information to decision-makers and interested stakeholders. The support tools, which will be built on open-source desktop GIS technology, will enable users to see, change, and display the geographic location on the map and conduct spatial query research
Keywords: Geographic Information System; Water Resource Management; Open Source GIS Software; Iraq